A Review of the Molecular Basis for Reduced Endometrial Receptivity in Uterine Fibroids and Polyps. Issue 4 (October 2017) - Narula, Shagun; Harris, Amani; Tsaltas, Jim
The presence of fibroids and endometrial polyps is associated with reduced endometrial receptivity and subsequent fertility outcomes. The following review explores the molecular mechanisms behind reduced endometrial receptivity, with a focus upon homebox genes, basic transcription element binding proteins, transforming growth factor β-3, and bone morphogenetic protein 2. A better understanding of these processes is essential for future targeted therapy.